EVALUATION OF BRINJAL (SOLANUM MELONGENA L.) GENOTYPES FOR HORTICULTURAL TRAITS UNDER HOT ARID ENVIRONMENT - MEENA, S.S.; VASHISHTHA, B.B.; Singh, R. K. (Annals of Agricultural Research, 2014)
Seventeen cultivars of brinjal were evaluated over two years under hot arid environment. The highest yield of 4.15 kg/plant was obtained from Pusa Uttam. The cultivar Pusa Ankur was earliest which took 42.33 days to first flower (DAS). Cultivar Arka Kusumakar expressed the maximum number of fruit (69.40 per plant) while cultivar Udaipur Local expressed the maximum weight (110 g). The cultivars IC-90984, Udaipur Local, Pusa Purple Cluster and Pusa Bhairav with moderately high yield of 3.53, 3.42, 3.33 and 3.25 kg/plant respectively, can be grown in addition to Pusa Uttam under hot arid environment.